2002
DOI: 10.1097/00000658-200208000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hepatic Venous Congestion: Proposed Indication Criteria for Hepatic Vein Reconstruction

Abstract: The state of venous congestion in the right liver graft can be correctly assessed by the temporary arterial clamping method and intraoperative Doppler ultrasonography. If the venocongestive area is demonstrated to be so large that the graft volume excluding this area is thought to be insufficient for postoperative metabolic demand, venous reconstruction is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
191
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 271 publications
(196 citation statements)
references
References 21 publications
2
191
0
3
Order By: Relevance
“…Although a proportion of patients do not require venous reconstruction despite deprivation of major venous drainage routes because of the presence of peripheral venous connections offering a bypass route for venous drainage, 27 such venous connections are typically thin and difficult to detect by preoperative imaging studies. Therefore, detailed surgical planning and knowledge of vascular anatomy is crucial for reducing surgical complications and poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although a proportion of patients do not require venous reconstruction despite deprivation of major venous drainage routes because of the presence of peripheral venous connections offering a bypass route for venous drainage, 27 such venous connections are typically thin and difficult to detect by preoperative imaging studies. Therefore, detailed surgical planning and knowledge of vascular anatomy is crucial for reducing surgical complications and poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…7 Other studies have suggested that the MHV tributaries should be reconstructed when the graft is small or the associated PV flow is regurgitated after clamping of the drainage veins. 8 In this case, the total calculated drainage area of the V5, V8, and 2 SHVs was as large as 58% of the total GV, for which reconstruction of all these tributaries was justified.…”
mentioning
confidence: 85%
“…The Model for End-Stage Liver Disease score was 9. Imaging studies revealed severe liver cirrhosis with 3 hypervascular nodules (maximum size, 2.3 cm) in segments 8,6, and 7 of the liver, which were compatible with hepatocellular carcinomas. An LDLT was indicated because of the expected poor prognosis with conventional therapeutic modality.…”
mentioning
confidence: 99%
“…1,2 Recent advances in imaging studies allow accurate estimations of regional liver volumes with postoperative venous occlusion after liver resection. 3 Methods to confirm such regions intraoperatively, however, have not yet been established.…”
Section: To the Editorsmentioning
confidence: 99%